Unlocking Potential of SME Business in Indonesia: A Holistic Transformative Business Coaching Model for Personal and Organizational Growth - Fu, Sucipto (Digital Repository of Theses, 2026)
This dissertation explores how Transformative Business Coaching (TBC) influences the psychological, emotional, and strategic development of Indonesian small and medium-sized enterprise (SME) owners. Drawing on transformative learning theory, self-determination theory, and concepts from emotional and energetic psychology, the study investigates three core questions: (1) How does TBC shape self-perception and entrepreneurial confidence? (2) What internal shifts occur during the coaching process? and (3) How does TBC impact business decision-making, team dynamics, and entrepreneurial practices? A qualitative, intervention-based case study design was employed, involving 30 SME owners across four Indonesian provinces. Participants took part in a three-day intensive coaching workshop, followed by a one-month online mentoring phase and a follow-up stage conducted one year later. Data were collected through reflective journals, emotional self-assessments, facilitator observations, and post-intervention interviews. The data were analyzed using a thematic analysis approach to identify patterns of psychological, emotional, and behavioral transformation. The findings reveal five interconnected domains of change: self-image, belief systems, emotional regulation, strategic clarity, and behavioral integration. Overall, TBC facilitated a progressive transformation process, beginning with internal emotional release and identity reconstruction, and developing into increased self-confidence, improved decision-making, strengthened leadership behaviors, and more positive team dynamics. These outcomes suggest that entrepreneurial success is strongly linked to inner psychological and emotional development, not only technical and strategic skills. This study contributes to the literature on entrepreneurship and coaching by demonstrating how integrative, transformative approaches—combining subconscious, emotional, and cognitive elements—can strengthen entrepreneurial resilience. Practically, the findings offer a replicable framework for coaching practitioners and provide insights for policymakers seeking to support holistic SME development. In increasingly complex and uncertain business environments, transformational coaching models such as TBC may play a critical role in fostering sustainable entrepreneurial growth and long-term impact. Keywords: Transformative Business Coaching, Entrepreneurial Mindset, Emotional Intelligence, SME Development, Identity Reframing, Coaching Intervention